Investigation of the Relationship Between Religious Attitude and Postpartum Physical and Perineal Pain in Iran - Dokuhaki, Sara (Journal of religion and health, 2023)
Postpartum pain is one of the most important and common problems of postpartum mothers who resort to non-pharmacological strategies to relieve it due to the side effects of painkillers. This study was conducted to investigate the relationship between religiosity and postpartum physical and perineal pain. The sample size in this cross-sectional study was 101 women giving birth in educational and medical centers of Shiraz, Iran, that was selected by purposive-convenience sampling. Then, a questionnaire was completed for each of them including demographic characteristics, religious attitude, and visual scale of postpartum pain. Data were analyzed by SPSS software. The frequency of the majority of the research population was found at moderate religious attitudes 65.4% (72 individuals). There is a positive and Statistical inverse correlation between religious attitude and perineal pain. According to Fisher's test, in mothers with a high religious attitude, 9.7% had severe perineal pain, 41.9% had moderate pain, and 48.4% had mild pain (p = 0.001). Besides, in the case of physical pain, 3.2%, 35.5%, and 61.3% had severe, moderate, and mild pain, respectively. Regarding physical pains, with the increase in the level of mothers' religious attitude, physical pains also decreased, but the statistical relationship was not significant (p = 0.32). The results showed that the religiosity and spirituality of pregnant women have relieving effects on postpartum pain. Therefore, more attention to the spiritual dimension of human existence and planning to improve it using prayer therapy, dhikr, and meditation is suggested as a strategy to deal with the fear of pain and childbirth and reduce psychological and physical changes before and after childbirth. These findings apply to women with ectopic pregnancies in Iran.